Migratory dental implant in the maxillary antrum: a case report - Farhan Raza Khan; Haji, Zainab; Aysha Arif; Siddiqui, Humayun Kaleem (Journal of the Pakistan Medical Association, 2023)
Dental implants offer a predictable solution for the replacement of missing dentition. This report describes the case of a patient who underwent dental implant surgery several years ago but due to negligence on the part of previous dentist, her implant pushed into the maxillary sinus. The patient presented with vague pain and swelling in the right maxillary region. Orthopantomogram (OPG) showed that the implant was lying in the right maxillary sinus which the patient had no clue of. It was decided to retrieve the implant and later restore the missing teeth for definitive function and aesthetics. However, at the time of surgery, the implant in question was missing from the anticipated position as it had migrated to the most posterior-superior compartment of the antrum making its retrieval difficult in the first attempt. Later, a maxillofacial surgeon carried out the retrieval. —Continue